English Translated Manhwa to Enhance Students’ Literacy - Setyaningrum, Riya Risqi; Anam, Mukhtarul; Maimun, Misbach (Universitas PGRI Madiun, 2024)
The objective of this research was to investigate the effect of using English translated Manhwa on the students‟ literacy at junior high school. It was experimental research. The sample of this research was third grade students of Junior High School in SMP NEGERI 1 Kepohbaru, Bojonegoro in the academic year 2023/2024 with the total 48 students. Two groups were divides by total sampling. The first group was experimental group which was given treatment by English translated Manhwa and second group was control group which was not given treatment by using English translated Manhwa. The instrument of collecting data was a test consisted of 10 multiple items and 10 essay items. Each group was given a pretest and post-test. After the data had been collected, then the data was analysed by using SPSS. There was a significant effect of Using English translated Manhwa to the students‟ literacy. The conclusion from the data analysis is the value of t-test (0.133) is higher than the t-table (0.05). The result showed that H1 was accepted. Based on the result of this research, it was concluded that there was a significant effect of using English translated Manhwa on the students‟ literacy both reading and writing.